2008
DOI: 10.1111/j.1755-3768.2007.01161.x
|View full text |Cite
|
Sign up to set email alerts
|

Will improvement of knowledge lead to improvement of compliance with glaucoma medication?

Abstract: ABSTRACT.Purpose: To identify specific items on knowledge and need for information that could be used to improve compliance with glaucoma medication. Methods: Forty-four randomly selected ophthalmologists assigned 166 consecutive glaucoma patients to complete a questionnaire. The questionnaire was developed systematically based on focus group interviews, consultation of experts and a pilot test. Items included knowledge about glaucoma and its treatment, need for information and compliance with therapy. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 41 publications
1
29
0
3
Order By: Relevance
“…16,26 Our intervention involved a number of elements, but these were centred around a prescriptive assessment of health-care needs and beliefs on which education and ongoing support was based. Although education is frequently highlighted as being important in improving adherence, 7,27 we feel as others do, 6,28 that education alone may not adequately tackle the problem.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16,26 Our intervention involved a number of elements, but these were centred around a prescriptive assessment of health-care needs and beliefs on which education and ongoing support was based. Although education is frequently highlighted as being important in improving adherence, 7,27 we feel as others do, 6,28 that education alone may not adequately tackle the problem.…”
Section: Discussionmentioning
confidence: 99%
“…7,8 A systematic review found inconsistencies in the assessment of knowledge. 9 A survey by Hoevenaars et al 6 did not find an overall improvement in adherence with better education, but found certain factors to correlate with adherence, such as previous knowledge of glaucoma, social support, and fulfilled information needs. Patients' ability to manage glaucoma medications can differ according to their socioeconomic status, health-care experiences, and health beliefs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, improving education alone may not improve adherence levels; focusing on behavioural aspects may provide a more effective solution. 19 A patient-centred approach following an assessment of needs, health beliefs, and lifestyle may be the key to improving adherence and providing a lasting intervention effect. Further research is needed to enable eye care services to provide the most effective care for improving adherence levels for this patient group.…”
Section: Discussionmentioning
confidence: 99%
“…3,5,6,[19][20][21][22][23] One ophthalmic study objectively monitored doctor-patient interactions, 24 yet the authors are unaware of any studies that have objectively observed clinical consultations to compare the nature and depth of educational support provided with patients' knowledge of glaucoma and adherence to therapy. The aims of this survey were to investigate educational support, patients' knowledge, and self-reported adherence via observation and interview, to generate hypotheses about the impact of educational support on patients' knowledge of glaucoma and adherence, in preparation for an intervention study.…”
Section: Introductionmentioning
confidence: 99%